Electrochemical Determination of Organic Compounds in Automotive Fuels. Issue 2 (29th January 2014) - Santos, André L.; Takeuchi, Regina M.; Muñoz, Rodrigo A. A.; Angnes, Lúcio; Stradiotto, Nelson R.
Abstract This article critically reviews the electroanalytical methods devoted for the determination of organic compounds in automotive fuels that can range from contaminants to additives typically introduced into liquid biofuels and liquid fossil fuels. Contaminants such as aldehydes and ketones in bioethanol, free fatty acids and glycerol in biodiesel, and sulfur and nitrogen organic compounds in gasoline and diesel fuel, and additives such as colour markers and antioxidants added to fuels were determined by electroanalytical methods. Special focus is given to electrodes, electrochemical techniques, and sample preparation strategies. Future directions of research on electroanalysis of liquid fuels are presented.